In Situ Study of Coupled Mineral Dissolution and Precipitation Processes With Gas Production in Porous Media Using Magnetic Resonance Imaging - Lara Wegner; Andreas Pohlmeier; Yumeng Wang; Martina Klinkenberg; Dirk Bosbach; Jenna Poonoosamy (Water Resources Research, 2025)
Abstract Coupled mineral dissolution, precipitation, and gas exsolution (CDPG) are critical processes in subsurface energy applications. These phenomena occur during natural hydrogen degassing from serpentinized mafic rocks, anoxic corrosion of metallic nuclear waste canisters, and CO2 sequestration in deep saline aquifers. However, the behavior of exsolved gas within rock matrices remains poorly understood, particularly whether it is trapped by precipitates contributing to porosity clogging, or migrates with fluid flow and dissolves downstream. These uncertainties limit the accuracy of reactive transport models for predicting the long‐term evolution of such systems. Here, we developed a 3D reactive transport experiment to study the coupled dissolution of witherite (BaCO3), precipitation of barite (BaSO4), and exsolution of CO2. Magnetic resonance imaging (MRI) was used for live monitoring of heterogeneous gas production and transport, to quantify the relative gas content across the porous medium. In situ measurements of pH, pCO2, differential pressure, and effluent ion concentrations aligned with MRI findings that the dissolution‐precipitation process and gas exsolution lasted for 25 hr. Scanning electron microscopy showed porosity reduction resulted from barite precipitation in pore spaces and localized clogging from precipitation on CO2 bubble surfaces. Mineral dissolution is best modeled with a reactive surface area approach that accounts for mineral passivation. While permeability changes can be estimated using the Van Genuchten‐Mualem equation based on MRI‐measured water saturation in inert porous media, this method fails to account for changes in pore structures with mineral precipitation. These results provide a robust data set for benchmarking reactive transport models and advancing understanding of CDPG.